Concomitant dimorphs of tri-O-[p-halobenzoyl]-myo-inositol 1,3,5-orthoformates with different halogen bonding contacts: first order crystal-to-crystal thermal phase transition of kinetic form to the thermodynamic form - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S.; Sanki, A. K. (Chemical Communications, 2005)
Crystallization of tri-O-[p-halobenzoyl]-myo-inositol 1,3,5-orthoformates from ethyl acetate-petroleum ether solution produced concomitant dimorphs that have different halogen bonding contacts; the kinetic form with C-(BrO)-O-...-C contacts upon heating to 185 degrees C, converts completely to the thermodynamic form with C-(BrOLC)-O-... contacts via crystal-to-crystal first order phase transition.

Crystal-to-crystal transformation amongst dimorphs of racemic 2,6-di-O-(p-halobenzoyl)-myo-inositol 1,3,5-orthoformates that achieves halogen bonding contacts - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (CrystEngComm, 2008)
{Racemic 2,6-di-O-(p-halobenzoyl)-myo-inositol 1,3,5-orthoformates (bromo (1) and chloro (2)) produced two polymorphs each, thin needle type crystals (Form I) were obtained from methanol, whereas larger rectangular crystals (Form II) were produced from ethyl acetate. Both forms could be produced concomitantly on crystallization (of 1 or 2) from ethyl acetate-light petroleum ether mixture; the yield of Form II crystal was always much more compared to Form I crystals. Although, a one-dimensional isostucturality linking molecules via O-H center dot center dot center dot O hydrogen bonding is seen in both forms, the difference arises in linking these chains. In larger Form II crystals (of 1 and 2), the adhesions are via halogen bonding (C-X center dot center dot center dot O=C

Click synthesis of isomeric compounds for assessing the efficiency of the bifurcated Br center dot center dot center dot NO2 synthon - Ramana, C. V.; Chatterjee, Soumitra; Durugkar, Kulbhushan A.; Gonnade, Rajesh G. (Crystengcomm, 2009)
We report herein the extention of the azide-alkyne ``click reaction'' to crystal engineering and synthesize a collection of isomeric compounds with modular positioning of Br and NO2 on a tricyclic template and crystal structural analyses of the derived isomers. It is quite remarkable to notice that none of the isomers displayed the bifurcated three-center NO2 center dot center dot center dot Br supramolecular synthon in their crystal structures

Cu(I)-promoted one-pot `SNAr-click reaction' of fluoronitrobenzenes - Durugkar, Kulbhushan A.; Gonnade, Rajesh G.; Ramana, C. V. (Tetrahedron, 2009)
A one-pot two-step sequence involving a nucleophilic aromatic substitution (SNAF) of activated fluorobenzenes with azide nucleophile and in situ Huisgen cycloaddition of the resulting aryl azides with alkynes has been developed for a rapid access to 1,4-substituted triazoles. Control experiments revealed that both the steps are catalyzed by Cu(I) and also the course of reaction as SNAr followed by [3+2]-cycloaddition. (C) 2009 Elsevier Ltd. All rights reserved.

Catalytic asymmetric transfer hydrogenation of ketones using [Ru(p-cymene)Cl-2](2) with chiral amino alcohol ligands - Deshpande, Sudhindra H.; Kelkar, Ashutosh A.; Gonnade, Rajesh G.; Shingote, Savita K.; Chaudhari, Raghunath V. (Catalysis Letters, 2010)
Catalytic asymmetric transfer hydrogenation of aromatic alkyl ketones has been investigated using [Ru(p-cymene)Cl-2](2) and new derivatives of beta-amino alcohols synthesized from (S)-(-)-lactic acid and mandelic acid as ligands. Chiral secondary alcohols were obtained with good to excellent conversion (60-90%) and moderate to good enantioselectivities (40-86%). Asymmetric transfer hydrogenation of ketones has been investigated using [Ru(p-cymene)Cl-2](2) and beta-amino alcohols synthesized from (S)-(-)-lactic acid and Mandelic acid as ligands. Chiral secondary alcohols were obtained with good to excellent conversion (60-90%) and moderate to good enantioselectivities (40-86%).
Keywords: Amino alcohol ligand; Asymmetric transfer hydrogenation; Ketones; Ru catalyst

Conformational polymorphism in racemic 2,4-Di-o-Benzoyl-6-o-Tosyl myo-Inositol 1,3,5-Orthoacetate - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Journal of Structural Chemistry, 2010)
The title compound, C(29)H(26)O(10)S, yields two conformational polymorphs concomitantly from dichloromethane-methanol mixture; the major polymorph grows as plates (Form I, monoclinic, P2(1)/n) and the minor polymorph grows as needles (Form II, triclinic, P-1). The two forms differ mainly in orientation of the tosyl group. In Form I, sulfonyl oxygen of the tosyl group makes intermolecular C -HaEuro broken vertical bar O interactions, whereas the same group in Form II is involved in an intramolecular short dipolar S=OaEuro broken vertical bar C=O (sulfonyl-carbonyl) contact. The molecular organization and the influence of various weak non-covalent interactions that stabilize these conformers in the crystal lattices are discussed.
Keywords: Conformation; crystal structure; dipolar interactions; Inositol; non-covalent interactions; polymorphism; sulfonyl-carbonyl contact

Crystal structure, NMR and theoretical investigations on 2-(o-hydroxy-anilino)-1,4-napthoquinone - Feizi, Nourollah; Pinjari, Rahul V.; Gejji, Shridhar P.; Sayyed, Fareed B.; Gonnade, Rajesh G.; Rane, Sandhya Y. (Journal of Molecular Structure, 2010)
Crystal structure, (1)H NMR and cyclic voltammetric investigations of 2-(o-hydroxy-anilino)-1,4-napthoquinone (HAN), resulting from coupling of aminophenol with 2-hydroxy-1,4-napthoquinone, have been carried out. X-ray structure reveals that the HAN ligand crystallizes in orthorhombic space group Pca2(1) with Z = 4. forming a chain via inter-molecular O2 center dot center dot center dot H1A-O1 and C15-H15 center dot center dot center dot O3 interactions. Both (1)H NMR and cyclic voltammetry experiments suggest the titled ligand is associated and exists as dinner in d(6)-DMSO while the monomer has been predicted in CDCl(3) solution. Density functional calculations can be utilized to gauge the strength of hydrogen-bonded interactions from the (1)H chemical shifts in the NMR spectra. Self-consistent reaction field (SCRF) calculations further support the inferences drawn from cyclic voltammetry experiments. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: (1)H NMR; cyclic voltammetry; Density functional; hydrogen bonding; Napthoquinone

Crystal-to-crystal thermal phase transition amongst dimorphs of hexa-O-p-toluoyl-myo-inositol conserving two-dimensional isostructurality - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (Crystengcomm, 2010)
Triclinic (P-1) crystals of hexa-O-p-toluoyl-myo-inositol obtained from common organic solvents exhibited single crystal-to-single crystal irreversible phase transition centered at similar to 250 degrees C. The transformation of these crystals to monoclinic P2(1)/n form was revealed using DSC and X-ray diffraction studies. The latter crystals could also be produced by melt crystallization. Crystal structure analysis revealed that the molecules in both forms are linked via bifurcated C-H center dot center dot center dot O interactions to make almost identical centrosymmetric dimers. The neighbouring dimers are bridged via C-H center dot center dot center dot O and aromatic pi center dot center dot center dot pi stacking interactions to create two-dimensional isostructural assemblies. The difference in the two crystal forms arises from linking of the centrosymmetric dimers along the third dimension; the dimers are centrosymmetrically bridged in the triclinic form, while they have n-glide relationship in the monoclinic form. Comparison of the dimorph structures further revealed that they are actually an excellent case of morphotropism since dimorphs are related by non crystallographic rotation and translation of their basic motif (centrosymmetric dimers) that transforms the triclinic (P-1) phase to a monoclinic (P2(1)/n) phase.

Concurrent display of both alpha- and beta-turns in a model peptide - Srinivas, Deekonda; Vijayadas, Kuruppanthara N.; Gonnade, Rajesh G.; Phalgune, Usha D.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This article describes a model peptide that concurrently displays both alpha- and beta-turns, as demonstrated by structural investigations using single crystal X-ray crystallography and solution-state NMR studies. The motif reported herein has the potential for the design of novel conformationally ordered synthetic oligomers with structural architectures distinct from those classically observed.

Conformationally rigid aromatic amino acids as potential building blocks for abiotic foldamers - Ramesh, Veera V. E.; Roy, Arup; Vijayadas, Kuruppanthara N.; Kendhale, Amol M.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This communication describes the development of conformationally constrained unnatural aromatic amino acids, constructed on rigid backbone wherein the carboxyl and amino groups project in two dimensions (planes) on the aromatic framework. Such a feature offers the possibility of design and development of conformationally ordered synthetic oligomers with intriguing structural architectures distinct from those classically observed. Furthermore, such amino acids will have the potential to extend the conformational space available for foldamer design with diverse backbone conformation and structural architectures.

Chiral crystals from an achiral molecule: 4,6-di-O-benzyl-1,3-O-benzylidene-2-O-(4-methoxybenzyl)-myo-5-inosose - Gurale, Bharat P.; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Acta Crystallographica Section C-Crystal Structure Communications, 2012)
The title achiral compound, C35H34O7, crystallizes in the chiral monoclinic space group P21. The molecules are densely packed to form a helical assembly along the crystallographic twofold screw axis via CH...O and CH...p interactions. Interestingly, the unit-translated helical chains are loosely connected via a rather uncommon edge-to-edge PhH...HPh short contact (H...H = 2.33 angstrom).

Correlation of hydrogen-bonding propensity and anticancer profile of tetrazole-tethered combretastatin analogues - Jedhe, Ganesh S.; Paul, Debasish; Gonnade, Rajesh G.; Santra, Manas K.; Hamel, Ernest; Tam Luong Nguyen; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2013)
A series of 1,5-disubstituted tetrazole-tethered combretastatin analogues with extended hydrogen-bond donors at the ortho-positions of the aryl A and B rings were developed and evaluated for their antitubulin and antiproliferative activity. We wanted to test whether intramolecular hydrogen-bonding used as a conformational locking element in these analogues would improve their activity. The correlation of crystal structures with the antitubulin and antiproliferative profiles of the modified analogues suggested that hydrogen-bond-mediated conformational control of the A ring is deleterious to the bioactivity. In contrast, although there was no clear evidence that intramolecular hydrogen bonding to the B ring enhanced activity, we found that increased substitution on the B ring had a positive effect on antitubulin and antiproliferative activity. Among the various analogues synthesized, compounds 5d and 5e, having hydrogen-bonding donor groups at the ortho and meta-positions on the 4-methoxy phenyl B ring, are strong inhibitors of tubulin polymerization and antiproliferative agents having IC50 value in micromolar concentrations. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Colchicine; Combretastatin; Crystal; Tetrazole; Tubulin

Capturing a novel metastable polymorph of the anticancer drug gefitinib - Thorat, Shridhar H.; Patwadkar, Manjusha V.; Gonnade, Rajesh G.; Vaidhyanathan, R. (CrystEngComm, 2014)
Gefitinib, a life-extending anticancer drug, exhibits solvent-mediated conformational polymorphism to yield stable (form I) and novel metastable (form II) polymorphs. Crystal structure analysis revealed 3D isostructurality in the molecular organization of the polymorphs, and the metastable polymorph undergoes a crystal-to-crystal thermal phase transition to the stable polymorph.

Chiron approach to formal synthesis of both antipodes of cis 3-hydroxypipecolic acid - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N.; Dumare, Nilesh B.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Tetrahedron Letters, 2014)
The efficient and practical formal syntheses of both enantiomers of cis 3-hydroxypipecolic acid were accomplished from cis aziridine-2-carboxylate as the common synthetic precursor. The key steps involved are stereo and regioselective aziridine ring opening, reductive cyclization and selective N-debenzylation over O-debenzylation reactions. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 3-Hydroxypipecolic acid; Aziridine ring opening; Aziridine-2-carboxylate; Piperidine alkaloids; Selective debenzylation

Correlation of the solid-state reactivities of racemic 2,4(6)-di-O-benzoyl-myo-inositol 1,3,5-orthoformate and its 4,4 `-bipyridine cocrystal with their crystal structures - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Acta Crystallographica Section C-Structural Chemistry, 2014)
Racemic 2,4(6)-di-O-benzoyl-myo-inositol 1,3,5-orthoformate, C21H18O8, (1), shows a very efficient intermolecular benzoyl-group migration reaction in its crystals. However, the presence of 4,4 `-bipyridine molecules in its cocrystal, C21H18O8 center dot C10H8N2, (1)center dot BP, inhibits the intermolecular benzoyl-group transfer reaction. In (1), molecules are assembled around the crystallographic twofold screw axis (b axis) to form a helical self-assembly through conventional O-H center dot center dot center dot O hydrogen-bonding interactions. This helical association places the reactive C6-O-benzoyl group (electrophile, El) and the C4-hydroxy group (nucleophile, Nu) in proximity, with a preorganized El center dot center dot center dot Nu geometry favourable for the acyl transfer reaction. In the cocrystal (1)center dot BP, the dibenzoate and bipyridine molecules are arranged alternately through OH center dot center dot center dot N interactions. The presence of the bipyridine molecules perturbs the regular helical assembly of the dibenzoate molecules and thus restricts the solid-state reactivity. Hence, unlike the parent dibenzoate crystals, the cocrystals do not exhibit benzoyl-transfer reactions. This approach is useful for increasing the stability of small molecules in the crystalline state and could find application in the design of functional solids.
Keywords: acyl transfer; cocrystal; crystal structure; design of functional solids; helical assembly; hydrogen bonding; myo-inositol; solid-state reactions

Crystal-to-crystal thermal phase transformation of polymorphs of isomeric 2,3-naphthalene diol ditoluates: mechanism and implications for molecular crystal formation and melting - Tamboli, Majid I.; Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2014)
Isomeric para- (1) and meta- (2) ditoluate derivatives of naphthalene 2,3-diol exhibited polymorphism producing three (Forms 1I, 1II, 1III) and two (Forms 2I, 2II) polymorphs each, respectively, depending on the solvent and conditions of crystallization. Crystal forms 1I, 1II, and 2I could be obtained repeatedly, whereas crystal forms 1III and 2II were obtained (separately) in one of the crystallization experiments, each. All the crystal forms were stable at ambient conditions, except for Form 2II, which disintegrated to a powder over 45 days. In contrast, the ortho-ditoluate (3) of naphthalene 2,3-diol did not exhibit polymorphism; it yielded fibrous chiral crystals from different solvents/conditions. Crystal structure analysis of all these polymorphs revealed dominance of energetically similar weak intermolecular interactions such as CH center dot center dot center dot O, CH center dot center dot center dot pi, pi center dot center dot center dot pi, and their interplay in molecular aggregation resulting in polymorphic modifications. Differential scanning calorimetry (DSC), hot stage microscopy, single crystal and powder X-ray diffraction measurements revealed crystal-to-crystal thermal transformation of Forms 1I and 1II crystals to Form 1III crystals and Form 2II crystals to Form 2I crystals. The transformation of Form 1I and Form 1II crystals to Form 1III crystals can be viewed as progressive destabilization of the crystal lattice during heating and converting to metastable phase, whereas the conversion of Form 2II to Form 2I crystals can be considered as reorganization of an unstable crystalline phase to a stable crystalline phase. Hence comparative studies of the structure of stable, metastable, or transient crystals and crystal-to-crystal transformations involving these forms could aid in unraveling the process of crystallization.

Cu(II) conjugation along the transformation of a vitamin K-3 derivative to a dinaphthoquinone methide radical - Badave, Kirti D.; Patil, Shalaka S.; Khan, Ayesha A.; Srinivas, Darbha; Butcher, Raymond J.; Gonnade, Rajesh G.; Puranik, Vedavati G.; Pinjari, Rahul V.; Gejji, Shridhar P.; Rane, Sandhya Y. (New Journal of Chemistry, 2014)
1,1'-Methide-bi-vitamin K-3 (B) has been isolated as a dinaphthoquinone methide radical (DNQM) by the transformation of 1-imino(acetylhydrazino)-vitamin K-3 (A). The transformation follows a biomimetic activation pathway mediated via Cu(II) ion catalyzed oxidative coupling. Single crystal X-ray and electron spin resonance (ESR) experiments combined with density functional calculations elucidate the ``resonance structure'' of the DNQM radical (B). Fluorescence investigations reveal that DNQM facilitates interaction with the cysteine residue. As compared to the parent substrate, B shows a depletion in the level of GSH, triggering apoptosis in HeLa cells.

Catalyst-dependent selectivity in the relay catalytic branching cascade - Bansode, Avinash H.; Shaikh, Aslam C.; Kavthe, Rahul D.; Thorat, Shridhar; Gonnade, Rajesh G.; Patil, Nitin T. (Chemistry-A European Journal, 2015)
The synthesis of small organic molecules as probes for discovering new therapeutic agents has been an important aspect of chemical biology. One of the best ways to access collections of small molecules is to use various techniques in diversity-oriented synthesis (DOS). Recently, a new form of DOS, namely relay catalytic branching cascades (RCBCs), has been introduced, wherein a common type of starting material reacts with several scaffold-building agents (SBAs) to obtain structurally diverse molecular scaffolds under the influence of catalysts. Herein, the RCBC reaction of a common type of substrate with SBAs is reported to give two different types of molecular scaffolds and their formation is essentially dependent on the type of catalyst used.
Keywords: alkynols; cascade synthesis; chemoselectivity; diversity-oriented synthesis; Homogeneous catalysis

Cocrystallization of 2,3-dihydroxynaphthalene with its para-, meta-, and ortho-ditoluates: insight into cocrystal formation and clues for the construction of supramolecular assemblies capable of intermolecular acyl group transfer reactivity - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2015)
2,3-Dihydroxynaphthalene forms 2:1 cocrystals with its p-ditoluate and 1:1 cocrystals with its m-ditoluate but not with the o-ditoluate. In 2:1 cocrystals of the p-ditoluate, naphthalene diol molecules form a dimeric motif through OH...O hydrogen bonding interactions. The adjacent dimers sandwich the molecules of p-ditoluate through C-H...pi interactions. In 1:1 cocrystals of the m-ditoluate, naphthalene diol molecules generate a zigzag pattern through O-H...O hydrogen bonding interaction involving -OH of the diol and the C=O of the m-ditoluate. Intermolecular toluoyl group transfer reaction was more facile in cocrystals of the p-ditoluate as compared to cocrystals of the m-ditoluate. This difference in reactivity is consistent with the relative geometry of the electrophile (El, C-O) and the nucleophile (Nu, OH) in these cocrystals. A comparison of the cocrystallization behavior and structure of the two cocrystals with their constituents suggests that the position of the methyl group is crucial for cocrystal formation. A survey of the CSD revealed that the incidence of polymorphism and cocrystals formation decreases (number of hits) in the order para- > ortho- > meta- for disubstituted benzene derivatives. This suggests that compounds prone to exhibit polymorphism have more propensities to form cocrystals as compared to those that resist polymorphism. This information could be useful while selecting cocrystal formers and construction of supramolecular functional assemblies with desired properties.

Crystal structures of the pyrazinamide-p-aminobenzoic acid (1/1) cocrystal and the transamidation reaction product 4-(pyrazine-2-carboxamido)-benzoic acid in the molten state - Thorat, Shridhar H.; Sahu, Sanjay Kumar; Gonnade, Rajesh G. (Acta Crystallographica Section C-Structural Chemistry, 2015)
The synthesis of pharmaceutical cocrystals is a strategy to enhance the performance of active pharmaceutical ingredients (APIs) without affecting their therapeutic efficiency. The 1: 1 pharmaceutical cocrystal of the antituberculosis drug pyrazinamide (PZA) and the cocrystal former p-aminobenzoic acid (p-ABA), C7H7NO2- C5H5N3O, (1), was synthesized successfully and characterized by relevant solid-state characterization methods. The cocrystal crystallizes in the monoclinic space group P21/n containing one molecule of each component. Both molecules associate via intermolecular O-H center dot center dot center dot O and NH center dot center dot center dot O hydrogen bonds [O center dot center dot center dot O = 2.6102 (15)angstrom and O-H center dot center dot center dot O = 168.3 (19)degrees; N center dot center dot center dot O = 2.9259 (18) angstrom and N-H center dot center dot center dot O = 167.7 (16)degrees] to generate a dimeric acidamide synthon. Neighbouring dimers are linked centrosymmetrically through N-H center dot center dot center dot O interactions [N center dot center dot center dot O = 3.1201 (18) angstrom and N-H center dot center dot center dot O = 136.9 (14)degrees] to form a tetrameric assembly supplemented by C-H center dot center dot center dot N interactions [C center dot center dot center dot N = 3.5277 (19) angstrom and C-H center dot center dot center dot N = 147 degrees]. Linking of these tetrameric assemblies through N-H center dot center dot center dot O [N center dot center dot center dot O = 3.3026 (19) angstrom and N-H center dot center dot center dot O = 143.1 (17)degrees], NH center dot center dot center dot N [N center dot center dot center dot N = 3.221 (2) angstrom and N-H center dot center dot center dot N = 177.9 (17)degrees] and C-H center dot center dot center dot O [C center dot center dot center dot O = 3.5354 (18) angstrom and C-H center dot center dot center dot O = 152 degrees] interactions creates the twodimensional packing. Recrystallization of the cocrystals from the molten state revealed the formation of 4-(pyrazine-2-carboxamido) benzoic acid, C12H9N3O3, (2), through a transamidation reaction between PZA and p-ABA. Carboxamide (2) crystallizes in the triclinic space group P1 with one molecule in the asymmetric unit. Molecules of (2) form a centrosymmetric dimeric homosynthon through an acid-acid O-H center dot center dot center dot O hydrogen bond [O center dot center dot center dot O = 2.666 (3) angstrom and O-H center dot center dot center dot O = 178 (4) degrees]. Neighbouring assemblies are connected centrosymmetrically via a C-H center dot center dot center dot N interaction [C center dot center dot center dot N = 3.365 (3) angstrom and C-H center dot center dot center dot N = 142 degrees] engaging the pyrazine groups to generate a linear chain. Adjacent chains are connected loosely via C-H center dot center dot center dot O interactions [C center dot center dot center dot O = 3.212 (3) angstrom and CH center dot center dot center dot O = 149 degrees] to generate a two-dimensional sheet structure. Closely associated two-dimensional sheets in both compounds are stacked via aromatic pi-stacking interactions engaging the pyrazine and benzene rings to create a threedimensional multi-stack structure.
Keywords: acid-amide hetero-synthon; active pharmaceutical ingredient (API); cocrystal; crystal structure; hydrogen bonding; molten-state reaction; powder diffraction; transamidation reaction

Comparative study of dG affinity vs. DNA methylation modulating properties of side chain derivatives of procainamide: insight into its DNA hypomethylating effect - Gawade, Rupesh L.; Chakravarty, Debamitra K.; Debgupta, Joyashish; Sangtani, E.; Narwade, S.; Gonnade, Rajesh G.; Puranik, Vedavati G.; Deobagkar, D. D. (RSC Advances, 2016)
Procainamide derivatives have been synthesized to investigate the role of side chains in modulating the DNA methylation level in cancer cells and gain insight into its mechanism of action. The synthesized derivatives comprised of flexible (dimethyl), constrained (pyrrolidine, piperidine, morpholine) and planar aromatic (pyridine, phenyl) side chain motifs. The affinity of procainamide and its derivatives towards the deoxyguanosine (dG) base in neutral form has been assessed by performing Differential Pulse Voltammetry (DPV) under physiological conditions. Further, molecular docking with hemimethylated CpG rich DNA acquired from an active mDNMT-1-DNA (PDB ID-4DA4) crystal structure, reveals their preferential non-covalent interaction with dG nucleobase in the intercalation cavity of the minor groove. Differential affinity of the derivatives to dG base in neutral and bound forms (DNA) is correlated with their DNA methylation modulating properties at sub-lethal concentrations. Among all the derivatives, a compound with an aromatic phenyl side chain (1) has shown a highest binding affinity for dG nucleobase in neutral form as well as for partially denatured CpG rich DNA which is attributed to the formation of p/p stacking interaction in addition to N-H/O hydrogen bonding with the pyrimidine ring of dG base. It also shows the highest cytotoxicity and global hypomethylation at a sub-lethal level in the MCF-7 cancer cell line compared to other derivatives and procainamide. A docking study has also illustrated the plausible structural basis of DNA methylation modulating a property of procainamide. Strong association of procainamide with dG bases of partially denatured CpG rich DNA via H-bonding and other non-covalent interactions may alter the active topology of DNA required by the DNA-binding regulatory proteins (e. g. DNMT-1) which is validated by a DNMT-1 inhibition assay. This systematic investigation leads to a new potent alternative to procainamide being found and gives a plausible insight into the DNA hypomethylating effect of procainamide.

Clues from crystal structures pave the way to access chiral myo-inositol derived versatile synthons: resolution of racemic 4-o-allyl-myo-inositol-1,3,5-orthoesters via corresponding dicamphanates by crystallization - Patil, Nivedita T.; Shashidhar, Mysore S.; Tamboli, Majid I.; Gonnade, Rajesh G. (Crystal Growth & Design, 2017)
Racemic 4-O-allyl-myo-inositol-1,3,5-orthoesters were resolved as the corresponding diastereomeric dicamphanates by crystallization from alcoholic solvents. Crystals of the two diastereomers of myo-inositol orthoacetate and one diastereomer each of myo-inositol orthoformate and myo-inositol orthobenzoate were obtained in >99% purity, on gram scale. The configuration of all these diastereomers was established by conversion to known chiral myo-inositol derivatives as well as by single crystal structure analysis. It is interesting to note that the procedures for the separation of diastereomeric myo-inositol orthoesters could be evolved due to the knowledge of crystal growth and crystal structures of inositol derivatives of comparable molecular structures. Due to the synthetic versatility of myo-inositol orthoesters, the methods described provide rapid and convenient access to a variety of chiral inositol derivatives with high synthetic potential.

Coumarin-appended stable fluorescent self-complementary quadruple-hydrogen-bonded molecular duplexes - Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Shinde, Dinesh R.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2017)
In this paper we report a coumarin-conjugated self-assembling system adorned with valuable features such as high duplex stability and a built-in fluorophore, which would augment its application potential. This system forms a highly :stalik molecular duplex in a nonpolar solvent (K-dim > 1.9 X 10(7) M-1 in CDCl3). Due to the fluorescent property of coumarin, these new structural motifs may find potential application in material chemistry and supramolecular chemistry.

Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule - Shivakumar, K.I.; Goudappagouda.; Gonnade, Rajesh G.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemical Communications, 2018)
We report a novel set of easily tailorable C-3 symmetric molecules with a pi-extended core and adorned with different thioalkyl groups, exhibiting solvatofluorochromic and amphoteric redox behaviour. The nearly planar core exhibits intermolecular face-to-face pi-stacking, S...S and intramolecular S...O interactions. Current-sensing atomic force microscopy studies revealed a high conductivity of similar to 0.15 mS cm(-1) in the undoped J-aggregate nanofibres of the thiopropyl appended gelator.

Conformational studies of Ant-Pro motif-incorporated cyclic peptides: gramicidin S and avellanin - Kotmale, Amol S.; Sangtani, Ekta; Gonnade, Rajesh G.; Sarkar, Dhiman; Burade, Sachin; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2018)
This paper reports conformational changes observed in cyclic bioactive peptides such as gramicidin S and avellanin upon incorporation of a pseudo-beta (C9) Ant-(D)Pro turn motif in their structural frameworks. Solution-state studies suggested that a synthetic gramicidin S analog exhibits a beta-sheet conformation with C9 and C17 intramolecular hydrogen bonding patterns, while its truncated analog disturbs the beta-sheet conformation. Structural details were obtained using a combination of CD studies, X-ray crystal structure studies and nOe-based MD simulation studies.

Cocrystallization of 2,3-dihydroxynaphthalene with its para-, meta-, and ortho-ditoluates: insight into cocrystal formation and clues for the construction of supramolecular assemblies capable of intermolecular acyl group transfer reactivity (vol 15, pg 12 - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2019)

Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule (vol 54, pg 212, 2018) - Shivakumar, Kilingaru I.; Goudappagouda; Gonnade, Rajesh G.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemical Communications, 2019)
Correction for `Conducting nanofibres of solvatofluorochromic cyclohexanetrione-dithiolylidene-based C-3 symmetric molecule' by Kilingaru I. Shivakumar et al., Chem. Commun., 2018, 54, 212-215.

Crystal engineering for intramolecular pi-pi stacking: effect of sequential substitution of f on molecular geometry in conformationally flexible sulfonamides - Shaikh, Samir R.; Gawade, Rupesh L.; Kumar, Deepak; Kotmale, Amol; Gonnade, Rajesh G.; Stuerzer, Tobias (Crystal Growth & Design, 2019)
A small library of ten sulfonamide derivatives comprising two aromatic rings was synthesized to investigate the effect of chronological positioning of the F-atom on the intramolecular pi-stacking assembly. The sequential positioning of F atoms was carried out on one of the aromatic rings that is linked to the sulfonamide moiety directly while the other aromatic ring (phenyl or pyridine) is linked by an ethyl spacer with the sulfonamide moiety. The ethyl spacer is provided to achieve the required flexibility so that both aromatic rings can bend to acquire syn conformation facilitated pi-stacking between electron-deficient and electron-rich aromatic rings. The idea was to study the interplay between hydrogen bonding and pi-stacking synthons in the conformationally flexible sulfonamide derivatives. The solid-state conformation of all the derivatives was investigated using the single-crystal X-ray diffraction technique. Crystal structure analysis revealed that the syn conformation was achieved only in trifluoro and pentafluoro sulfonamide derivatives with benzene substitution while in all other derivatives the molecules take either midway or anti conformations. None of the sulfonamide molecules with a pyridine moiety showed syn conformation. It could be because of the involvement of the pyridine N-atom in the hydrogen bonding dimeric synthon. The molecular conformation study in solution state using 2D NOESY and HOESY NMR experiments also substantiated syn conformation in a pentafluoro sulfonamide molecule with benzene substitution. The conformational analysis carried out employing density functional theory (DFT) calculations confirmed higher stability for the syn conformation over midway and anti orientations.

Cyanuric-chloride-mediated synthesis of 2-Aryl-3-tert-butoxycarbonyl-thiazolidine-4-carboxylic acid anilides: mechanistic, X-ray crystal structures and cytotoxicity studies - Jagtap, Rohidas M.; Shaikh, Samir R.; Gonnade, Rajesh G.; Raheem, Shabnam; Rizvi, Masood A.; Pardeshi, Satish K. (ChemistrySelect, 2019)
The `2R,4R'-2-aryl thiazolidine-4-carboxylic acid anilides (ATCAAs) were synthesized using cyanuric chloride (CC) as a clean and substoichiometric acid-amine coupling agent under optimized reaction conditions. The diesterphenol intermediate based mechanism is proposed and supported by spectral characterization of the intermediate. The single crystal X-ray structures of acid substrate (2R,4R)-3-(tert-butoxycarbonyl)-2-(2-methoxyphenyl)thiazolidine-4-carbox ylic acid (3 a) and anilides (R)-tert-butyl 4-(2-fluorophenylcarbamoyl)thiazolidine-3-carboxylate (4 b), (2R,4R)-tert-butyl 2-(2,6-dichlorophenyl)-4-(m-tolylcarbamoyl)thiazolidine-3-carboxylate (6 b) confirmed the formation of chiral anilides. The synthesized library of anilides [(R)-tert-butyl 4-Aryl thiazolidine-3-carboxylate and (2R,4R)-tert-butyl 2-Aryl-4-Aryl thiazolidine-3-carboxylate] 4 a-6 f was screened for their in vitro anti cancer, neuronal and neuroprotective studies. The anilides 4 b, 4 g, 5 d, 5 h, 6 c and 6 f (where the aryl=2-fluorophenylcarbamoyl, 4-chlorophenylcarbamoyl, 2-methoxyphenyl, 2,5-dichlorophenylcarbamoyl, 2,6-dichlorophenyl, 4-chlorophenylcarbamoyl respectively)were found to be less cytotoxic towards N2 A, SHSY-5Y neuronal cell lines in their differentiated and undifferentiated forms, and also exhibited dose dependant anti-inflammatory properties for a possible identification towards neurodegenerative and inflammatory disorders.
Keywords: Acid-amine coupling; Cyanuric chloride; Cytotoxicity; Mechanistic investigations; Single crystal x-ray structure

Chiron approach to formal synthesis of both antipodes of cis 3-hydroxypipecolic acid (vol 55, pg 6423, 2014) - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N.; Dumare, Nilesh B.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Tetrahedron Letters, 2020)

Crystal structure of a 1:1 co-crystal of the anti-cancer drug gefitinib with azelaic acid - George, Christy P.; Sangtani, Ekta; Gonnade, Rajesh G. (Acta Crystallographica Section E: Crystallographic Communications, 2020)
In the title co-crystal, C22H24ClFN4O3·C9H16O4, gefitinib (GTB; systematic name: quinazolin-4-amine) co-crystallizes with azelaic acid (AA; systematic name: nona-nedioic acid). The co-crystal has the monoclinic P21/n centrosymmetric space group, containing one mol-ecule each of GTB and AA in the asymmetric unit. A structure overlay of the GTB mol-ecule in the co-crystal with that of its most stable polymorph revealed a significant difference in the conformation of the morpholine moiety. The significant deviation in the conformation of one of the acidic groups of azelaic acid from its usual linear chain structure could be due to the encapsulation of one acidic group in the pocket formed between the two pincers of GTB namely, the morpholine and phenyl moieties. Both GTB and AA mol-ecules form N-H⋯O, O-H⋯N, C-H⋯O hydrogen bonds with C-H⋯F close contacts along with off-stacked aromatic π-π inter-actions between the GTB mol-ecules.

Crystal-to-crystal synthesis of helically ordered polymers of trehalose by topochemical polymerization - Hema, Kuntrapakam; Gonnade, Rajesh G.; Sureshan, Kana M. (Angewandte Chemie-International Edition, 2020)
The synthesis of crystalline helical polymers of trehalose via topochemical azide-alkyne cycloaddition (TAAC) of a trehalose-based monomer is presented. An unsymmetrical trehalose derivative having azide and alkyne crystallizes in two different forms having almost similar packing. Upon heating, both the crystals undergo TAAC reaction to form crystalline polymers. Powder X-ray diffraction (PXRD) studies revealed that the monomers in both the crystals polymerize in a crystal-to-crystal fashion; circular dichroism (CD) studies of the product crystals revealed that the formed polymer is helically ordered. This solvent-free, catalyst-free polymerization method that eliminates the tedious purification of the polymeric product exemplifies the advantage of topochemical polymerization reaction over traditional solution-phase polymerization.
Keywords: Click reaction; helical polymers; polysaccharide; topochemical reactions; trehalose

Chemistry, anti-diabetic activity and structural analysis of substituted dihydropyrimidine analogues - Bairagi, Keshab M.; Younis, Nancy Safwat; Emeka, Promise Madu; Venugopala, Katharigatta N.; Alwassil, I, Osama; Khalil, Hany Ezzat; Sangtani, Ekta; Gonnade, Rajesh G.; Mohanlall, Viresh; Nayak, Susanta K. (Journal of Molecular Structure, 2021)
In an effort to identify an anti-diabetic agent, a series of methyl/ethyl 4-(hydroxyphenyl)-6-methyl-2-oxo/thioxo-1,2,3,4 tetrahydropyrimidine-5-carboxylate analogues (4a-h) have been synthesized, purified, and characterized by using Fourier-Transform Infrared Spectroscopy (FT-IR) and NMR (H-1 and C-13). The synthesized compounds were screened for anti-hyperglycemic activity using Streptozotocin (STZ) induced diabetic rat model. The anti-hyperglycemic activity of dihydropyrimidine (DHPM) compound is mainly analyzed with the variation of substituents present on the phenyl ring and urea/thiourea group on pharmacophoric features. Further, the crystal structure and supramolecular characteristics of two compounds 4c and 4f were analyzed through a single-crystal X-ray method and the Hirshfeld Surface Analysis, which shows hydrogen bonding through N-H center dot center dot center dot O and N-H center dot center dot center dot S interactions with the formation of ring motif in the crystal structure. It is interesting to note that among the title compounds, the 4a, 4e, 4f, and 4g significantly displayed a better hypoglycemic effect in vivo rat model study. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Dihydropyrimidine (DHPM); Hypoglycemia; Streptozotocin (STZ); Type-2 diabetes mellitus (T2DM)

Construction of two-component chemically reactive supramolecular assemblies-acyl migration reactions in cocrystals of napthalene-2,3-diol and its diesters - Bahadur, Vir; Gonnade, Rajesh G.; Tamboli, I. Majid; Krishnaswamy, Shobhana; Shashidhar, Mysore S. (ChemPlusChem, 2021)
Reactions in solids are of contemporary interest due to applications in pharmaceutical industries to environmental sustainability. Although several reactive crystals that support chemical reactions have been identified and characterized, the same cannot be said about reactive cocrystals. Earlier we correlated the facile acyl group transfer reactions in crystals with supramolecular parameters obtained from the crystal structures. The structure-reactivity correlation revealed the requirement of proper juxtaposition of electrophile (C=O) and the nucleophile (OH) with distance (similar to 3.2 angstrom) and angle (similar to 90 degrees) along the chain structure. The current article describes the preparation of cocrystals that are capable of supporting intermolecular acyl group transfer reactions in a group of structurally similar molecules. The cocrystals of naphthalene 2,3-diol and its corresponding diesters showed a facile solid state acyl transfer reaction, which has been well correlated with their crystal structures.
Keywords: Acylation; domino reactions; intermolecular interactions; reaction in cocrystal; solid-state reactions; X-ray diffraction

Controlled di-lithiation enabled synthesis of phosphine-sulfonamide ligands and implications in ethylene oligomerization - Mote, Nilesh R.; Gaikwad, Shahaji R.; Khopade, V, Kishor; Gonnade, Rajesh G.; Chikkali, Samir H. (Dalton Transactions, 2021)
Catalyst design for ethylene oligomerization has attracted significant interest. Herein, we report the synthesis of phosphine-sulfonamide-derived palladium complexes and examine their performance in ethylene oligomerization. Arresting a dilithiation intermediate of N-(2-bromophenyl)-4-methylbenzenesulfonamide (1) at -84 degrees C selectively produced N-(2-(bis(2-methoxyphenyl)phosphanyl)phenyl)-4-methylbenzenesulfonamide (L1A). However, the same reaction at -41 degrees C delivered a different ligand; 2-(bis(2-methoxyphenyl)phosphanyl)-4-methyl-N-phenylbenzenesulfonamide (L2A). The generality of our strategy has been demonstrated by preparing N-(2-(diphenylphosphanyl)phenyl)-4-methylbenzenesulfonamide (L1B) and 2-(diphenylphosphanyl)-4-methyl-N-phenylbenzenesulfonamide (L2B). Subsequently, L1A and L1B were treated with a palladium precursor to yield 5-membered complexes C1 and C2, respectively. In contrast, L2A upon treatment with palladium produced a 6-membered metal complex C3. Thus, a small library of 7 palladium complexes (C1-C7) were synthesized by varying the donor moiety (pyridine, DMSO, and acetonitrile). The identity of palladium complexes was unambiguously ascertained using a combination of spectroscopic and analytical methods, including single-crystal X-ray diffraction. The performance of the complexes C1-C7 was investigated in ethylene oligomerization and almost all of them were found to be active. The resultant ethylene oligomers were characterized using H-1 and C-13 NMR, MALDI-ToF-MS, and GPC. Detailed screening of reaction parameters revealed 100 degrees C and 40 bars ethylene to be optimal conditions. Complex C5 outperformed other complexes and produced ethylene oligomers with a molecular weight of 1000-1900 g mol(-1).

cis-aziridine synthon based synthetic investigation for tamiflu employing horner-wadsworth-emmons reaction - Chavan, Subhash P.; Kawale, Sanket A.; Gonnade, Rajesh G. (European Journal of Organic Chemistry, 2022)
Synthetic investigations to achieve a novel intermediate of Tamiflu by using cis-aziridine as a chiral building block, which is readily synthesized from (D)-mannitol as a renewable starting material, has been presented. The present approach utilizes the intramolecular Horner-Wadsworth-Emmons reaction as the key step for the synthesis of Tamiflu. On the other hand, diene containing allylic aziridine framework is found to be inefficient to furnish the six-membered core skeleton of Tamiflu through ring-closing metathesis reaction.
Keywords: Aziridine; cyclization; HWE reaction; Metathesis; Tamiflu

Chemodivergent coupling of azoarenes with benzyl alcohols via a borrowing hydrogen strategy using a well-defined nickel catalyst - Bansal, Sadhna; Gonnade, Rajesh G.; Punji, Benudhar (Catalysis Science & Technology, 2023)
Chemodivergent (de)hydrogenative coupling of azoarenes with benzyl alcohols is achieved via the N=N bond activation using an inexpensive and well-defined (6-OH-bpy)NiCl2 catalyst. This protocol highlights the construction of C-N bonds via a borrowing hydrogen strategy that offers substituted imines and amines. A range of azo compounds couple with various substituted benzyl alcohols in a tandem hydrogenation/dehydrogenation process. The nickel catalyst along with the K2CO3 or (KOBu)-Bu-t base governed the selectivity in imine and amine formation. A preliminary mechanistic study establishes the crucial role of metal-ligand cooperation (MLC) comprising the distinct radical pathways.

Cocrystal approach to modulate the photoluminescent properties of a GFP chromophore analogue: role of halogen/hydrogen bonding in achieving a wide range of solid-state fluorescence emissions - Mali, Bhupendra P.; Dash, Soumya Ranjan; Annadhasan, Mari; Biswas, Anupam; Manoj, Kochunnoonny; Vanka, Kumar; Gonnade, Rajesh G. (Crystal Growth & Design, 2023)
Fine-tuning the photophysical properties of fluorescentorganicsolids is essential to attain multicolor displays and meet the demandfor futuristic light-emitting materials. Here, we report the tunableluminescence of a green fluorescent protein (GFP) chromophore analogue,3,4,5-TIA (A), based on the formation of two-component molecular cocrystalswith six different coformers. Coformers selected to synthesize thebinary cocrystals include 1,4-diiodotetrafluorobenzene (B), perfluoronaphthalene(C), 1,4-dibromotetrafluorobenzene (D), 2,3,5,6-tetrafluoroterephthalicacid (E), benzene-1,2,4,5-tetracarbonitrile (F), and benzene-1,2,4,5-tetracarboxylicacid (G). Interestingly, the cocrystals A center dot C and A center dot Fshowed molecular crystal polymorphism with a slight variation in fluorescence,revealing an aggregation-induced emission (AIE). A crystal structureanalysis showed the interplay of hydrogen bonding, halogen bonding,and aromatic pi-stacking interactions in associating neutralsolid components in the cocrystal. All of the novel cocrystals displayeda wide range of photoluminescence ranging from blue to dark orange.The time-dependent density functional theory (TD-DFT) calculationsindicate the changes in the energy level structures (HOMO to LUMO)in cocrystals that resulted in variations in fluorescence emission.The study aims to further understand the structure-propertyrelationship between molecular arrangement and photoluminescence. Cocrystals of a GFPc analogue with differentcoformers displayeda wide range of fluorescence emissions ranging from blue to dark orangewith varying quantum yields. With similar geometries of pi-stackinginteractions, hydrogen and halogen bonding have played a vital rolein fine-tuning the photoluminescence; halogen bonding leads to a blueshift, and hydrogen bonding results in a red shift.

On the competition between six-membered and five-membered NHC towards alane centered ring expansion - Balayan, Kajal; Sharma, Himanshu; Vanka, Kumar; Ravindranathan, Sapna; Gonnade, Rajesh G.; Sen, Sakya S. (Chemical Communications, 2023)
The combination of 6-SIDipp center dot AlH3 (1) and 5-IDipp resulted in the ring expansion of 6-NHC, while the five-membered NHC remained unchanged, which was subsequently explained by DFT studies. Besides, the substitution chemistry of 1 was also studied with TMSOTf and I-2, which gave rise to the substitution of a hydride by triflate or iodide ligands.

Catalytic cycloisomerization-oxidative cyclization reaction sequence of enyne diesters derived from 2-propargyloxyarylaldehydes - Prajapati, Karmdeo; Saini, Manoj Kumar; Gonnade, Rajesh G.; Basak, Ashok K. (Organic Letters, 2024)
Enyne diesters derived from 2-propargyloxyarylaldehydes are converted into 2-oxopyranochromenes via In(OTf)3-catalyzed cycloisomerization and 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ)-mediated oxidative cyclization reaction sequence in one pot. The process possesses broad substrate scope and good functional group compatibility and generates various 4-(hetero)aryl-substituted 2-oxopyranochromenes in 32-79% yields (over two steps). 2-Oxopyranochromenes undergo selective decarboxylation under Krapcho conditions. When treated with aliphatic secondary amines in DMF, 2-oxopyranochromenes undergo decarboxylative amination at ambient temperature to generate 2-amino-substituted functionalized chromenes in good yields.

Chelation-assisted and steric-controlled selectivity in the Pd-catalyzed C-H/C-H oxidative coupling of indoles - Vijaykumar, Muniyappa; Pradhan, Chandini; Gonnade, Rajesh G.; Punji, Benudhar (Chemical Communications, 2024)
We report the first regioselective C2-C7 oxidative coupling of indoles using a palladium catalyst upon the strategic installation of N-pyridinyl and C3-carbonyl, which delivers 2,7-biindoles with a broad scope (25 examples; up to 93% yield). Isolation of the catalytic intermediate reveals the initial activation of the C(7)-H bond, followed by the C(2)-H bond in indoles, and the reaction proceeds via a Pd(ii)/Pd(0) pathway. This manuscript describes the first regioselective C2-C7 oxidative coupling of indoles using a palladium catalyst through the strategic installation of N-pyridinyl and C3-carbonyl, which delivers diverse biorelevant 2-7-biindoles.

Crystal engineering for intramolecular π-π stacking: effect of substitution of electron-donating and electron-withdrawing groups on the molecular geometry in conformationally flexible Sulfoesters and sulfonamides - Shaikh, Samir R.; Gawade, Rupesh L.; Dabke, Niteen B.; Dash, Soumya R.; Vanka, Kumar; Gonnade, Rajesh G. (CrystEngComm, 2024)
A series of 21 sulfoester and sulfonamide derivatives comprising two aromatic rings was synthesized to investigate the effect of the presence of either electron-donating (ED) or electron-withdrawing (EW) groups on the intramolecular pi-stacking assembly. The positioning of ED or EW moieties was carried out directly on one of the aromatic rings linked to the sulfonyl or sulfonamide moieties. In contrast, the other aromatic ring (phenyl or pyridine) was connected by a -CH2-CH2- spacer with the sulfonyl or sulfonamide moiety. The purpose of having an ethyl spacer between the two aromatic rings was to achieve conformational flexibility, facilitating the intramolecular pi-stacking assembly between the two aromatic rings. The use of sulfoester/sulfonamide groups allowed more conformational flexibility to attain desired orientations in solids with the interplay of the hydrogen-bonding interactions. Between the two functional groups, sulfonamides offered a more hydrogen-rich environment due to the amine moiety and may exhibit higher H-bonding propensity than the sulfoester moiety. The central idea here was to study the interplay between the hydrogen-bonding and pi & ctdot;pi interactions. The substituent groups chosen were categorized as strong electron-withdrawing (-CF3 and -CN), weak electron-withdrawing (-Cl and -Br), neutral (-H), and good electron-donating (-CH3 and -OCH3) groups. Crystal structure analysis revealed the syn conformation for all the derivatives, enabling intramolecular pi & ctdot;pi interactions between the two aromatic rings, whereas in the sulfonamide derivatives, the molecule takes either midway or anti conformations, except for one pyridine sulfonamide derivative, which showed the syn orientation but lacked intramolecular pi-stacking interactions. The absence of any conventional H-bond forming functional groups in the sulfoester derivatives may have resulted in the syn geometry facilitated by intramolecular pi-stacking interactions. Conversely, H-bond-forming functional groups in the sulfonamide derivatives could have prevented the syn conformation. The conformational analysis carried out employing density functional theory (DFT) calculations confirmed the higher stability of the syn conformation over the midway and anti orientations. The placing of electron-withdrawing and electron-donating groups at the para position of the benzene revealed sulfoesters preferably adopts a syn geometry facilitating the intramolecular pi-stacking, but sulphonamides takes midway or anti-geometry.

Catalyst and transition-metal free 1,6-conjugate addition of azobisisobutyronitrile: access to isobutyronitrile containing diarylmethanes - Mamale, Ajay G.; Ghodake, Balaji M.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Organic & Biomolecular Chemistry, 2025)
A catalyst and transition-metal free 1,6-conjugate addition of azobisisobutyronitrile to para-quinone methides for the synthesis of isobutyronitrile containing diarylmethanes has been achieved. This protocol enables the synthesis of isobutyronitrile containing diarylmethanes in good yields and with a broad substrate scope. This is the first example wherein azobisisobutyronitrile has been used as a cyanide source for 1,6-conjugate addition under catalyst and metal-free conditions.

Cocrystals of the green fluorescence protein chromophore analogue: coformer-induced switch between AIE and ACQ - Suresh, Sneha; Dabke, Niteen B.; Pandya, Rinu; Vanka, Kumar; Dutta, Madhusudan; Gonnade, Rajesh G. (Crystal Growth & Design, 2025)
Fluorescent organic solids hold great potential for advancing photonics applications. However, tuning their solid-state photoluminescent emissions remains a significant challenge. In this study, we report the synthesis and characterization of five cocrystals (two cocrystal polymorphs) derived from a pristine imidazolinone derivative (A) and the various coformer molecules, namely 1,2,4,5-tetrafluoro-3,6-diiodobenzene, 1,2,4,5-tetrafluoro-3,6-dibromobenzene, perfluoronaphthalene, and 3,4,5-trifluorobenzoic acid. The structural and optical properties of these cocrystals were examined by using single-crystal X-ray diffraction, absorption spectroscopy, photoluminescence spectroscopy, and photoluminescence decay spectroscopy. Cocrystals I, II, and III are isomorphous pairs and exhibit three-dimensional isostructurality, where the coformer molecules bridge adjacent helices of compound A, leading to aggregation-induced emission. In contrast, the cocrystal polymorphs IVA and IVB developed using coformer 3,4,5-trifluorobenzoic acid form two-dimensional sheet-like structures mediated by pi-stacking interactions between the coformers and molecule A, with interplanar distances ranging from 3.2 to 3.5 & Aring;. These stronger pi-pi interactions promote nonradiative decay pathways, resulting in reduced or quenched fluorescence and an aggregation-caused quenching effect. To gain further insights into their electronic properties, theoretical analysis including frontier molecular orbitals, time-dependent density functional theory, Hirshfeld surface analysis, molecular electrostatic potential, and noncovalent interaction plots were performed.

Cocrystals of the highly potent sickle cell anemia drug voxelotor with trimesic acid: a substantial enhancement in in vitro dissolution performance at physiological pH - Khan, Akram A.; Shaikh, Tabrez R.; George, Christy P.; Gonnade, Rajesh G. (Crystal Growth & Design, 2025)
Global Blood Therapeutic's (GBT's) Voxelotor is an investigational oral therapy for treating sickle cell anemia. It functions by increasing the affinity between hemoglobin and oxygen, thereby preventing the sickling of red blood cells and altering the disease's pathology. The US FDA has approved Voxelotor for the treatment of sickle cell anemia and granted it an orphan drug status. However, Voxelotor is classified as a BCS class II, indicating poor water solubility. The current study explores the enhancement of Voxelotor's water solubility by forming cocrystals with trimesic acid (TMA). Novel cocrystals, cocrystal solvates, and hydrates of Voxelotor (Vox) with trimesic acid (TMA) have been developed to improve their solubility. The new solids were characterized using PXRD, DSC, TGA, XPS, HSM, and single-crystal X-ray diffraction studies, and the intermolecular interactions were quantified using Hirshfeld surface analysis. Detailed crystallographic analysis revealed strong O-H center dot center dot center dot N hydrogen bonding interactions between Vox and TMA, primarily involving the COOH functional group of TMA and the pyridine or pyrazole groups of Vox. Additionally, TMA molecules participate in further hydrogen bonding-either with themselves or with solvates, including hydrates, through mono- or dimeric O-H center dot center dot center dot O H-bonding synthons. In vitro solubility studies demonstrated a significant increase in the solubility of Voxelotor in the Vox-TMA cocrystals compared to the pristine drug at physicochemical pH 4.5 and 6.8. Stability studies confirmed that the nonsolvated multicomponent crystal retains their structural integrity under nonambient conditions without undergoing polymorphic phase transitions. In contrast, the solvated crystals, including hydrates, undergo phase transitions within the temperature range of 100-130 degrees C, losing solvents and converting into one of the nonsolvated cocrystal forms. These findings suggest that the novel Vox-TMA cocrystals have the potential to enhance the therapeutic performance and clinical utility of Voxelotor.